Antibacterial and antibiofilm properties of salvadora persica extracts against carbapenem-resistant acinetobacter baumannii isolated from endotracheal tube samples - Alias, Wan Alif Syazwani Wan (2024)
Carbapenem-resistant Acinetobacter baumannii (CRAB) is one of the pathogens that is difficult to eradicate from the surrounding and resist all antibiotics. As a result, CRAB may cause serious and deadly infections in patients under treatment in hospitals. Salvadora persica (S. persica) roots have been used for maintaining oral hygiene and the World Health Organization (WHO) has recommended them. It has the potential to be used in research and studies related to medicine. This study aimed to elucidate the antibacterial and antibiofilm properties of the most effective solvent extract of S. persica roots against CRAB isolated from endotracheal tube (ETT) samples. Three different solvents (hexane, chloroform and methanol) were used in the Soxhlet apparatus to extract S. persica. Gas chromatography-mass spectrometry (GC-MS) was used to analyze each extract, and characterized by library databases. Benzoic acid, fatty acids, alcohols, and vitamin E were among the phytochemical compounds found in the various solvent extracts of S. persica that had been analyzed by GC-MS. Benzoic acid was the main compound found in hexane and chloroform extract, while glycerol was main compound found in methanol extract. Broth microdilution assay was used to evaluate the antimicrobial activity of extracts against CRAB to determine the minimum inhibitory concentration (MIC) values. While, minimum bactericidal concentration (MBC) assay was used to determine the concentration needed to eradicate CRAB. The Minimum biofilm inhibition concentration (MBIC) assay and minimum biofilm eradication concentration (MBEC) assay were used to identify the antibiofilm activity of CRAB. Then, the ultrastructure of the biofilm was analyzed using scanning electron microscopy (SEM). Hexane was selected as the most efficient solvent due to their lowest MIC and MBC values (1.56-3.13 mg/ml and 6.25-12.50 mg/ml, respectively). While, MBIC and MBEC values were 6.25 mg/ml and 62.5-125.00 mg/ml, respectively. Antimicrobial and antibiofilm activity of all selected CRAB (n=20) were identified (MIC=1.56- 6.25 mg/ml; MBC=3.13-12.50 mg/ml; MBIC=6.25- 25.00 mg/ml; MBEC=12.50- 62.50 mg/ml). SEM shows reduction effect after treated with the extract. In conclusion, various phytochemical compounds that have antibacterial properties were extracted from different solvents. From this study, extracts containing hexane demonstrated the most effective antibacterial and antibiofilm properties against CRAB. By using hexane solvent, the results show significant antibacterial and antibiofilm properties against CRAB.